Gestión de inventario y el capital de trabajo en empresas del sector de la construcción - Jácome Nieto, Elizabeth Monserrate (2022)
This research work was carried out in companies in the construction sector in the north of Guayaquil, in order to evaluate the inventory management system and determine how it affects the working capital of said company; For this, information gathering techniques and instruments were developed; the work is composed as follows: In Chapter I, the research problem, objectives, justification and the idea to defend are detailed...........